(untitled) - Morra-Imas, Linda G. (Washington, DC, 2009)
This comprehensive text presents concepts and procedures for evaluation in a development context. It provides procedures and examples on how to set up a monitoring and evaluation system, how to conduct participatory evaluations and do social mapping, and how to construct a "rigorous" quasi-experimental design to answer an impact question.
Keywords: Economic development,Phát triển kinh tế; Evaluation,Đánh giá